Design and control of a piezo-driven flexure micromanipulator for the embryo biopsy - Zhang, Zezhong (Nanyang Technological University, 2020)
Trophectoderm (TE) biopsy is the most common method of embryo biopsy for Pre-implantation Genetic Testing (PGT). One of the critical problems in TE biopsy is how to dissect the zona pellucida (ZP) membrane of the embryo with minimal cell deformation, which requires high-precision micromanipulation. Instead of going with the more common approach of burning embryo by laser, we adopted a cheaper and more easily controlled piezo-driven mechanical approach by using the high-frequency axial and lateral vibration of the end-effector, the micropipette tip. It is challenging to control vibrations of the tip since the slender tip is easy to involve bending. This thesis focuses on the design and control of a piezo-driven flexure micromanipulator to control the vibration of micropipette tips and perform the embryo dissection. The designed micromanipulator consists of a piezoelectric actuator, a flexure mechanism, a micropipette, and a connector. A two-stage embryo dissection strategy is proposed. First, we penetrate a hole on the surface of the embryo in the axial direction, and then enlarge the hole by lateral cutting. By utilizing the resonant vibration at corresponding driving frequencies in different axes, the flexure mechanism is designed to guide the micropipette tip to accomplish the desired vibrations described in the strategy. A method is proposed to control the vibrations of the micropipette tip and to dissect the embryo based on the micromanipulator. By setting the parameters of driving frequency of 4, 400 Hz and the driving voltage of 50 V of the piezoelectric actuator, mouse embryos are dissected with little cell deformation (less than 5 µm) under the proposed procedure, in which the driving voltage is applied suddenly and a slight cell deformation is pre-pressed (3~5 µm). In this work, a reliable piezo-driven flexure micromanipulator has been developed. It dissected the mouse embryo with an effective control method. It can be utilized to decrease the cost and to simplify the process for future embryo biopsy.